Evaluating the impact of school decentralization on education quality - Galiani, Sebastian (2001)
An important piece of the major fiscal and structural reforms undertaken in Argentina in the early 1990's was the decentralization of education services from the federal government to the provincial governments. The theoretical literature does not find absolute superiority of centralization or decentralization in the provision of public services. We evaluate empirically the effect of the decentralization of secondary schools in Argentina on education quality. Our results suggest that, on average, decentralization improved the performance of public school students in test scores. We also explore whether the effect of decentralization depends on province characteristics. We find that the effect is positive when schools are transferred to fiscally ordered provinces, but negative when provinces run significant fiscal deficits.